KNOWLEDGE, ATTITUDE, AND AWARENESS OF WARNING SIGNS AND RISK FACTOR OF LIVER CIRRHOSIS AND DIABETES MELLITUS AMONG SECOND YEAR DENTAL STUDENTS - A SURVEY (Journal of Pharmaceutical Negative Results, 2022)
Background: Cirrhosis of the liver is otherwise known as liver cirrhosis or hepatic cirrhosis is the condition when our liver is damaged for the long term. Liver cirrhosis contributes to 23.59% of mortality in the world and it is also ranked 27th as a major cause of death in the world. The most common liver cirrhosis is pathogenic and nonpathogenic. Like more than 30 % of people are having liver cirrhosis with diabetes mellitus (DM). Most liver cirrhosis diseases can lead to diabetes which causes hepatogenous diabetes (HD). Our study aims to create awareness about the risk factor of liver cirrhosis and diabetes mellitus among second-year dental students. Method: The survey on awareness of risk factors of liver cirrhosis and diabetes mellitus among the second-year dental students was conducted using a google form link. This study was conducted among 100 second-year dental students. A questionnaire related to liver cirrhosis was collected with options related to the symptoms, causes, treatments, and outcomes of liver cirrhosis and diabetes. .SPSS version 21.0 (IBM Inc, Armonk, NY, USA ). Pie charts and Bar diagrams were used to represent output variables.Result : The graph depicted that the main reason due to liver cirrhosis is 51.43 % said liver failure, 31.43 % said liver problem, 11.43 % said all of these, 5.71 % said liver disease. It shows the survival rate of persons suffering from liver cirrhosis , 71.43 % said 60 % -90 % , 20.00 % said 10 % -30 % , 8.57 % said 30 % - 60 % . We have seen the association between gender and awareness of liver cirrhosisConclusion : We can conclude that most of the students are aware of diabetes mellitus and how it can lead to liver cirrhosis. Reason: They need to be educated about the risk factors and complications of liver cirrhosis. Awareness camps, social media, workshops, seminars should be conducted to create more awareness on how diabetes mellitus can lead to liver cirrhosis.